Edukasi SADARI (pemeriksaan payudara sendiri)di Kelurahan Murni Kota Jambi - Nurfitriani Nurfitriani (Jurnal Abdimas Kesehatan (JAK), 2020)
Breast cancer is a condition in which cells develop abnormally so that they form a mass of malignant tissue entering the surrounding tissue and can spread throughout the body. Of the 10 types of cancer in the world, breast cancer is the second largest with 12.90% of deaths after lung cancer. While the prevalence of cancer in Indonesia, Jambi Province ranks 13th out of 34 provinces in Indonesia with 1287 patients in 2017 (Jambi Provincial Health Office Data, 2017). Kelurahan Murni one of Kelurahan in Danau Sipin Subdistrict, where there are still many communities in the region who do not understand breast self-examination as a detection of breast cancer. Based on field observations, it was found that the Posbindu group was not optimal in organizing educational activities for the community due to the lack of knowledge of theKader well as the optimal health center program that supervises them. The targets of this community service activity are Kader Posbindu  and group in the Kelurahan Murni. This activity aims to increase the knowledge of kader and group Kelurahan Murni socialization BSE as an early detection of Breast Cancer in the form of education, socialization and demonstration of Breast Self-Examination (BSE), with the hope that kader  and group are able to understand and be motivated to do BSE every month so as to prevent early prevention. the incidence of breast cancer and 100% increased knowledge of the participants.